AGAMA DAN KEHIDUPAN EKONOMI MENURUT SJAFRUDDIN PRAWIRANEGARA - Anwar Abbas (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2013)
Sjafruddin Prawiranegara, a national leader and economic scholar, has been recognized his expertise in managing the economy of Indonesia. However, many people do not yet comprehend his concepts of economic thought, linking him to Islam. Sjafruddin was belief of the truth of his religion and for that reason, he invited Muslims to believe the teachings of his religion. To that end, according to Sjafruddin, Muslims should bring out his religion teaching in organizing and managing its economic life. Thus, all economic activities of Muslims should be accordance with the provisions of his religion.DOI: 10.15408/aiq.v5i1.2556